Research priorities for respiratory nursing: a UK-wide Delphi study. Issue 2 (20th April 2018) - Kelly, Carol Ann; Kirkcaldy, Andrew J.; Pilkington, Melissa; Hodson, Matthew; Welch, Lindsay; Yorke, Janelle; Knighting, Katherine
Respiratory nurses make a significant contribution to the delivery of respiratory healthcare, but there is a dearth of nurse-led, practice-focused, published research. Using a modified three-round Delphi, this study sought to identify research priorities for respiratory nursing to inform a national research strategy. Study information and the survey link were sent electronically to members of UK professional respiratory organisations. Round 1 had 78 items across 16 topics, informed by a systematic literature review. Respondents suggested additional items which were content analysed to inform Round 2. Respondents rated all items and ranked the topics in all rounds. To ensure rigour, rounds had an explicit focus with pre-determined criteria for consensus (70%). In total, 363 responses were received across Rounds 1, 2 and 3 (n=183, 95 and 85, respectively). The top five research priorities were: 1) "Patient understanding of asthma control"; 2) "The clinical and cost-effectiveness of respiratory nurse interventions"; 3) "The impact of nurse-led clinics on patient care"; 4) "Inhaler technique"; and 5) two topics jointly scored: "Prevention of exacerbations" and "Symptom management". With potential international significance, this is the first UK study to identify research priorities for respiratory nursing, providing direction for those planning or undertaking research. UK-wide Delphi survey identifies nursing research priorities to enhance respiratory care for patients and carers http://ow.ly/ekGt30iXYXt